Factor Influence User’s Intention to Continue Use of Mobile Payment in Indonesia: Fintech Perspective - Abdullah Syakur Novianto; Ratna Tri Hardaningtyas; Puji Handayati; Agus Hermawan (International Journal of Economics, Business and Innovation Research, 2023)
This research aims to examine the influence of perceived usefulness and perceived ease of use on consumer attitude and the influence of consumer attitude on continuance intention among mobile payment users in Indonesia. Primary data was obtained by distributing online questionnaires to mobile payment users. Partial least squares–structural equation modelling (PLS-SEM) is used to test the influence of perceived usefulness and perceived ease of use on consumer attitude as well as the influence of consumer attitude on continuance intention of mobile payment. The results of this research are that perceived usefulness was found to have no effect on consumer attitude and continuance intention of mobile payment. Perceived ease of use was found to have a significant positive effect on consumer attitude. Likewise, consumer attitude was found to have a significant positive effect on the continuance intention of mobile payment.